HIV Clients as Agents for Prevention: A Social Network Solution - Ssali, Sarah; Wagner, Glenn; Tumwine, Christopher; Nannungi, Annette; Green, Harold (AIDS research and treatment, 2012)
HIV prevention efforts to date have not explored the potential for persons living with HIV to act as change agents for prevention behaviour in their social networks. Using egocentric social network analysis, this study examined the prevalence and social network correlates of prevention advocacy behaviours (discussing HIV in general; encouraging abstinence or condomuse, HIV testing, and seeking HIV care) enacted by 39 HIV clients in Uganda. Participants engaged in each prevention advocacy behaviour with roughly 50–70% of the members in their network. The strongest determinant of engaging in prevention advocacy with more of one’s network members was having a greater proportion of network members who knew one’s HIV seropositive status, as this was associated with three of the four advocacy behaviours. These findings highlight the potential for PLHA to be key change agents for HIV prevention within their networks and the importance of HIV disclosure in facilitating prevention advocacy.
Keywords: HIV Clients; Agents; Social Network Solution